Recovery of banana seedlings from waterlogging stress with pseudostem residue - Lima, Juliana Domingues [UNESP]; Passos da Conceição, Mariana [UNESP]; Rozane, Danilo Eduardo [UNESP]; Modenese-Gorla da Silva, Silvia Helena [UNESP]; Nardini Gomes, Eduardo [UNESP]; da Silva Baldinotti, Heloisa [UNESP] (Revista Mexicana de Ciencias Agricolas, 2024)
Floods are increasing worldwide because of the climate change. On the other hand, it is necessary to provide an adequate destination for the large amount of residue produced after banana harvesting. The objective of this study was to evaluate the effect of pseudostem residue on the recovery of banana seedlings subjected to waterlogging. The experiment was carried out in Registry, SP, Brazil, in a greenhouse, in the autumn and spring in 2021, using a design in divided plots with two factors and six repetitions. Waterlogging treatment was carried maintaining a layer of water in pots for three days (72 h). After drainage, pseudostem residue was added to half of the pots. seven days after the start of recovery, detected reduction of 20.3% in height and 28.7% in leaf area, accumulation of soluble carbohydrates in roots and leaves in autumn, reduction in chlorophyll, N, Mg and Zn contents, as well as the activity of POD, SOD and APX enzymes in roots and leaves. The residue proved to be beneficial after stress due to a 37.8% increase in the root area, recovery of Mg and Zn levels in root and leaf, prevention of elevation of activity of POD and SOD enzymes in leaves, APX in root. In the absence of stress, it reduced the activity of antioxidant enzymes; therefore, it should be used regardless of crop area be subject waterlogging.
Recuperación de plántulas de banano del estrés por inundaciones con residuos de pseudotallos
Keywords: banana waste; estrés abiótico; flooding; Musa spp